(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In order to compare some objects and statements we need the structure of the degrees Of Comparison. The structure of the analytical degrees of comparison is meaningfully overt; these forms are devoid of the feature of "semantic idiomatism" characteristic of some other categorial analytical forms, such as, for instance, the forms of the verbal perfect. For this reason the analytical degrees of comparison invite some linguists to call in question their claim to a categorial status in English grammar.